2020
DOI: 10.1002/jdn.10001
|View full text |Cite
|
Sign up to set email alerts
|

Exercise before pregnancy attenuates the effects of prenatal stress in adult mice in a sex‐dependent manner

Abstract: The present study aimed to investigate the long‐term effects of exercise before pregnancy on changes induced by prenatal stress. Female and male Balb/c mice were divided into three groups: control (CON), prenatal restraint stress (PNS), and exercise before the gestational period plus PNS (EX + PNS). As adult, fear/anxiety behavior, corticosterone secretion, expression of hypothalamic‐pituitary‐adrenal (HPA)‐related genes, as well as epigenetic modifications were evaluated. Exercise before gestation did not pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…On the other hand, evidence in the literature demonstrates that gestational stress is related to an increased risk of developing asthma and other diseases, including mental disorders and morphological and structural alterations in the hippocampus (Burgueno et al., 2020; Turcotte‐Tremblay et al., 2014). Nevertheless, the results presented here indicate beneficial effects of maternal treadmill exercise on inflammatory markers in the brain of prenatally stressed mice, corroborating a previous study in which exercise has been shown beneficial by helping to prevent the effects caused by stress in adult mice (Luft et al., 2020). The impacts of prenatal stress and the possible effects of physical exercise on lung tissue still need to be further investigated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, evidence in the literature demonstrates that gestational stress is related to an increased risk of developing asthma and other diseases, including mental disorders and morphological and structural alterations in the hippocampus (Burgueno et al., 2020; Turcotte‐Tremblay et al., 2014). Nevertheless, the results presented here indicate beneficial effects of maternal treadmill exercise on inflammatory markers in the brain of prenatally stressed mice, corroborating a previous study in which exercise has been shown beneficial by helping to prevent the effects caused by stress in adult mice (Luft et al., 2020). The impacts of prenatal stress and the possible effects of physical exercise on lung tissue still need to be further investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Convincing data demonstrate that physical exercise during the gestational period may be considered a form of treatment and prevention to the development of chronic diseases (Lee et al., 2016). Therefore, the use of physical exercise to counterbalance stressful situations may induce positive effects, such as a better ability to regulate glucocorticoid secretion, which can benefit neural, cardiovascular, and metabolic functions, in addition to helping to modulate the inflammatory process (Luft et al., 2020; Marcelino et al., 2015; Stranahan et al., 2008). However, few studies have examined the effects of maternal physical exercise on the response of inflammatory and HPA axis markers.…”
Section: Introductionmentioning
confidence: 99%
“…9 Both repeated variable prenatal stress and restraint prenatal stress are well-established protocols used in several studies. 8,13,27,28 Although differences regarding the time and frequency of the repeated restraint stress exposure exist, several studies have demonstrated that its use during pregnancy leads to impaired spatial learning and memory, anxiety, increased corticosterone levels, among others. 29,30 Moreover, it is well established that exposure to adverse events during the prenatal period is considered to generate alterations in both body weight and composition.…”
Section: Discussionmentioning
confidence: 99%
“…12 We have recently shown that pregestational exercise attenuates the effects of prenatal stress in the offspring, in a sex-dependent manner. 13 However, the long-term effects of exercise before pregnancy and the possible mechanisms involved in the metabolic response are not yet well elucidated. Nevertheless, persistent effects of exercise have been related to cognitive improvement in rats 14 and the attenuation of posttraumatic stress symptoms in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal stress was performed as described previously (Luft, Levices, da Costa, et al, 2020; Luft, Levices, Pedrazza, et al, 2020). Briefly, pregnant mice were restrained for 30 minutes, on intercalated days, from the 8th day of gestation.…”
Section: Methodsmentioning
confidence: 99%